The Effectiveness of Using Semantic Mapping Strategy in Teaching Reading Comprehension of Narrative Text - Afriyanti (Journal of Innovative and Creativity, 2023)
This research was aimed to investigate the effectiveness of using semantic mapping strategy in teaching reading comprehension of narrative text and the significant difference on reading comprehension of narrative text between two groups: who were taught using semantic mapping strategy and those who were taught using quick reading method. The design of this study was experimental study. The population of this study was the eighth grade students of SMP 3 Bonai Darusalam in the academic year of 2023. The number of the subjects was 60 students. The data were obtained by administering reading test to the VIII B as control group and VIII C as experimental group. The research was started by giving pre-test, treatments, and post-test to both experimental and control groups. The data of the test were analyzed by using t-test formula to know the difference of the students’ comprehension in reading narrative text between two groups. In the pre-test, the average score of the experimental group was 51.2667 and the control group was 64. The average score of post-test of the experimental group was 76. 0667 while the control one was 70.6667. The result of the t-test of mean difference was 8.939 and t-table was 2.00. It means that t-value is higher than t-table (8.939>2.00). The calculation revealed that the hypothesis about a significant difference on reading comprehension between students who were taught narrative text by using semantic mapping strategy and those who are taught by using quick reading method was accepted. Based on the research conducted, it was proved that the use of semantic mapping strategy is effective as a strategy to improve teaching reading achievement of narrative text to the eighth year students of SMP 3 Bonai Darusalam.